An Analysis of Employment Preferences: A Study of Marriage and Family Therapy Students - Christian, Sarah (My University, 2015)
The objective of the project is to determine how Marriage and Family Therapy students feel about employment opportunities with small businesses versus larger corporations. After obtaining IRB approval, a survey was distributed to Marriage and Family Graduate Programs across the country. They were asked to complete this survey based off of their employment preferences upon graduation. These students were in either their first or second year of graduate school, preparing to be therapists soon. The study was designed to determine if therapists want to go into small practices, doing more nonprofit type work, or if they ultimately want to go to a larger practice where they could potentially make more money. This survey also showed the business savvy of these students, and if they are treating this career the same as they would if they were going in to the business world. Based off the sample size, students agreed that if you valued money, job security, and greater fringe benefits then you work for a large company. However, the majority also agreed that you would have better managerial relationships, more responsibilities, and involvement in decision-making in a small company.
Keywords: Employment; Therapy; Business